(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The author’s vision onto nature and essence of the Female’s and Male’s begins as a key constants of people’s being, is shown in article. A comparative analysis of the two cultural eras on a large scale, namely, matriarchy and patriarchy, is carrying out. It substantiates the position that the passing from the fateful childhood through the beautiful youth, humanity has entered a new stage, namely post-patriarchy or neomatriarchy, that synthesizes the spiritual experience of the previous cultural and historical eras. In a statement of this futurological project the standard philosophical and culturological methodology of the analysis in civilization and regional perspectives is applied (in the context of the Kazakh philosophy, language and ethnic mentality). For its justification the comparative analysis of the international universal concept «ан» ([`ʌn]), which rise to parent language of archaic communities, is carried out also. Thus, the provision of neomatriarchy as new step of mankind’s spiritual evolution is reasoned. Key words: «Ана» [ʌn`ʌ] (Mother), matriarchy, patriarchy, neomatriarchy, love, Morality- Mercy, new generation.